The Virgin Embracing the Virgin: Eugenio Cajés' Short-Lived Iconography of Our Lady del Sagrario in Counter-Reformation Toledo. Issue 6 (3rd July 2019) - Cavero de Carondelet, Cloe
Abstract: This article examines the remarkable scene of The Virgin Embracing Our Lady del Sagrario of Toledo represented in a little-known drawing by the royal painter Eugenio Cajés now preserved in the Biblioteca Nacional in Madrid. This unique drawing is the only known image that depicts the moment in which the Virgin honoured one of her sculpted effigies with her touch. After reconstructing the religious and political context of the episode's invention in sixteenth-century Toledo, the article goes on to analyse the textual and other sources used by the artist to create this new religious iconography. As a detailed case-study, it thus offers a significant new contribution to the debate on the invention and reception of sacred images in post-Tridentine Spain.